Analisis Transformational Leadership terhadap Kinerja PNS dan PPPK Generasi Z pada Pemerintah Kabupaten Tulungagung - Sismonica, Ardinatul; Rusandy, Deby Santyo (Universitas Islam Kadiri, 2026)
This research aims to describe and analyze the differences in the influence of transformational leadership on the performance of generation z civil servants and Government Employees with Employment Agreements in Tulungagung Regency Government. The increasing composition of generation z civil servants and Government Employees with Employment Agreements requires regional leaders to be more adaptive and inspiring, considering that this generation has different characteristics from previous generations. This type of research is quantitative with a comparative approach (comparing). The independent variable (x) in the form of transformational leadership style and the attachment variable in the form of civil servant and Government Employees with Employment Agreements performance are used as research objects. The research instrument used a questionnaire. Data analysis techniques include instrument testing, descriptive statistics, classical assumption testing, simple linear regression twice and hypothesis testing. Research results (1) Transformational leadership style has a positive and significant effect on the performance of generation z civil servants (2) Transformational leadership style has a positive and significant effect on generation z PPPK performance (3) There is a difference in the magnitude of the influence of transformational leadership style on performance between the generation z civil servant and Government Employees with Employment Agreements groups